Evaluasi dan Pengembangan Kebijakan Pendidikan Agama Islam (PAI) - Gunarti Sukriyatun; Sofyan Sauri; Sutarman Sutarman (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The purpose of this study is to determine the evaluation and development of Islamic education policies, to provide input to policy makers to take better steps. Evaluation is to determine the ability of students before taking lessons, as well as determining the field of study or majors that they will choose. Fourth, diagnostic evaluation, which is an evaluation aimed at knowing and analyzing the condition of students, both with regard to the difficulties encountered, as well as the obstacles encountered in teaching and learning activities. The research method used is qualitative with document study. Documents in the form of Regulation of the Minister of Religion, Director General of Education at the Ministry of Religion of the Republic of Indonesia, and Islamic Religious Education policies implemented in Schools/Madrasahs, other documents that support research on the implementation of Islamic Religious Education policies implemented in Madrasas. The results of this study are first, evaluation and development of education, assessment and measurement of all components of education implementation, in the form of improvements and changes that occur in students after they take part in learning. Second, evaluation and development of education in Islam is very necessary, with the aim of providing the best service for students, improving and developing education to suit the times. Third, in terms of objectives, evaluation consists of formative, summative, placement, and diagnostic evaluations. Fourth, evaluation and development must be carried out based on certain conditions and principles so that the evaluation results can be acknowledged as true, and accepted by the parties concerned. Keyword: evaluation; policy; education.